Isolation and characterization of the Escherichia coli htrB gene, whose product is essential for bacterial viability above 33 degrees C in rich media. - Karow, M (1991)
We have identified and studied the htrB gene of Escherichia coli. Insertional inactivation of the htrB gene leads to bacterial death at temperatures above 33 degrees C. The mutant bacterial phenotype at nonpermissive temperatures includes an arrest of cell division followed by the formation of bulges or filaments. The htrB+ gene has been cloned by complementation and shown to reside at 23.4 min on the E. coli genetic map, the relative order of the neighboring loci being mboA-htrB-pyrC. The htrB gene is transcribed in a counterclockwise fashion, relative to the E. coli genetic map, and its product has been identified as a membrane-associated protein of 35,000 Da. Growth experiments in minimal media indicate that the HtrB function becomes dispensable at low growth rates.